Implementasi Akhlakul Karimah Melalui Outbound di Sekolah Alam Lampung (Studi Kasus di Sekolah Alam Al-Karim Lampung dan Sekolah Alam Lampung) - Mulyana, Agus; Kholid, Idham; Septuri, Septuri (CV. Creative Tugu Pena, 2024)
The aim of this research is to determine and analyze the implementation of morals through outbound at the Alam Lampung School. This research is included in field research and the type of research used is qualitative research. The data presentation in this research uses descriptive data presentation using interview, observation and documentation methods. The results obtained in this research are Al Karim Lampung Natural School and Lampung Natural School which have four additional curriculum models besides the curriculum 2013, namely the Islamic Morals Curriculum, Science Logic Curriculum, Leadership Curriculum, and Entrepreneurship Curriculum. Outbound is a learning method in the open that can shape students' character, especially morals, through direct experience which is expressed through the learning process carried out. Keywords: Implementation, Outbound, Akhlakul Karimah